Zen of the plains: discovering space, place and self - Olstad, Tyra A. (Kansas State University, 2012)
With their windswept ridges and wind-rent skies, prairies and plains have often been denigrated as nothing but nothing—empty, meaningless, valueless space. Mountains and forests, oceans and deserts have been praised and protected while vast expanses of undulating grasslands have been plowed under, grazed over, used, abused, maligned. Once the largest ecosystem on the North American continent, wild prairies now persist mainly in overlooked or unwanted fragments. In part, it’s a matter of psychology; some people see plains as visually unpleasing (too big, too boring) or physically alienating (too dry, too exposed). It’s also part economics; prairies seem more productive, more valuable as anything but tangles of grass and sage. But at heart, it’s a matter of sociocultural and individual biases; people seeking bucolic or sublime landscapes find “empty,” treeless skyscapes flat and dull, forgettable. Scientific, social, and especially aesthetic appreciation for plains requires a different perspective—a pause in place—an exploration of the horizon as well as an examination of the minutiae, few people have strived to understand and appreciate undifferentiated, untrammeled space. This research seeks to change that by example, using conscientious, systematic reflection on first-hand experience to explore questions fundamental to phenomenology and geography—how do people experience the world? How do we shape places and how do places shape us?—in the context of plains landscapes. Written and illustrated from the perspective of a newcomer, a scholar, a National Park Service ranger, a walker, a watcher, a person wholly and unabashedly in love with wild places, the creative non-fiction narratives, photoessays, and hand-drawn maps address themes of landscape aesthetics, sense of place, and place-identity by tracing the natural, cultural, and managerial histories of and personal relationships with Arizona’s Petrified Forest National Park, South Dakota’s Badlands National Park, Kansas’s Konza Prairie Long-Term Ecological Research Station, and Wyoming’s Fossil Butte National Monument. Prosaic and photographic meditations on wildness and wilderness, travel and tourism, preservation and conservation, days and seasons, expectations and acceptance, even dreams and reality intertwine to evoke and illuminate the inspiring aesthetic of spacious places—Zen of the plains.
Keywords: Sense of place; Landscape perception; National park service; Environmental history -- Great Plains; Nature writing; Prairie; Aesthetics (0650); Environmental Studies (0477); Geography (0366)